E-FACILITATION`S RIPPLE EFFECT ON EDUCATIONAL TRANSITION - Javed, Amna; Kohda, Youji (PUPIL: International Journal of Teaching, Education and Learning, 2024)
The rapid evolution of the online learning environment has stimulated an increased reliance on effective e-facilitation to enhance the educational experience. Employing a mixed-methods approach, the data were collected from the observation of a virtual workshop and questionnaires distributed to the participants through an online survey tool. The research investigates how the quality of e-facilitation influences the psychological safety perceptions of participants and subsequently affects their willingness to share knowledge. The study suggests that e-facilitation acts as a catalyst, creating a ripple effect on the psychological safety climate within online learning communities. By fostering a supportive and inclusive digital atmosphere, e-facilitators contribute to learners’ sense of security, encouraging open communication and collaboration. Furthermore, the research investigates into the impact on knowledge-sharing behavior, clarifying the mechanisms through which e-facilitation facilitates the exchange of ideas, experiences, and insights among participants. The findings of this study have practical implications for educators, instructional designers, and e-facilitators seeking to optimize online learning environments.